Advanced Glycation Endproducts and Alendronate Differentially Inhibit Early and Late Osteoclastogenesis in vitro - Gangoiti, María Virginia (2013)
Advanced Glycation Endproducts (AGEs) are greatly elevated in bone extracellular matrix of patients with Diabetes mellitus, and this has been associated with the increased incidence of fractures observed in these patients. AGEs affect the homeostasis of bone cells such as osteoblasts and osteoclasts. Bisphosphonates are first-line anti-osteoporotic drugs that principally exert their effects by inhibiting osteoclastic activity. However, the effect of bisphosphonate treatment on bone quality in patients with Diabetes is uncertain. In the present work we have evaluated the action of AGEs (50-200 μg/ml), with or without Alendronate (10-8-10-4M), on osteoclastogenesis induced by co-cultures of Raw 264.7 macrophages and UMR106 osteoblasts. We determined the effects of different culture conditions on osteoclastic recruitment, tartrate-resistant acid phosphatase (TRAP) activity and expression of RAGE (receptor for AGEs); and on the osteoblastic expression of RANK ligand (RANKL). AGEs and Alendronate inhibited the recruitment and TRAP activity of osteoclasts, with an additive effect of both agents at high concentrations of Alendronate. While AGEs prevented the early and late stages of osteoclastogenesis, Alendronate (alone or in co-incubation with AGEs) only inhibited its later stages. In addition, both AGEs and Alendronate increased the osteoclastic expression of RAGE and decreased the osteoblastic expression of RANKL, correlating closely with their inhibition of osteoclastogenesis. If these in vitro results can be extrapolated to a clinical setting, they may be indicating a potentiation of the anti-resorptive effects of Alendronate in the context of bone extracellular matrix with excess accumulation of AGEs, as might occur in a patient with Diabetes mellitus.